Bacterial infections and outcomes of inpatients with COVID-19 in the intensive care unit during the delta-dominant phase: the worst wave of pandemic in Iran - Akbari, Mojtaba; Dehghani, Yeganeh; Shirzadi, Mohammad; Pourajam, Samaneh; Hosseinzadeh, Majid; Sajadi, Mahdi; Alenaseri, Malihe; Siavash, Mansour; Jafari, Leila; Solgi, Hamid (Frontiers in Public Health, 2024)
Background Epidemiological data regarding the prevalence of bacterial multidrug-resistant (MDR) Gram-negative infections in patients with COVID-19 in Iran are still ambiguous. Thus, in this study we have investigated the epidemiology, risk factors for death, and clinical outcomes of bacterial infections among patients with COVID-19 in the intensive care unit (ICU). Method This retrospective cohort study included patients with COVID-19 hospitalized in the ICU of a university hospital in Iran between June 2021 and December 2021. We evaluated the epidemiological, clinical, and microbiological features, outcomes and risk factors associated with death among all COVID-19 patients. Data and outcomes of these patients with or without bacterial infections were compared. Kaplan–Meier plot was used for survival analyses. Results In total, 505 COVID-19 patients were included. The mean age of the patients was 52.7 ± 17.6 years and 289 (57.2%) were female. The prevalence of bacterial infections among hospitalized patients was 14.9%, most of them being hospital-acquired superinfections (13.3%). MDR Klebsiella pneumoniae and Staphylococcus aureus were the most common pathogens causing respiratory infections. Urinary tract infections were most frequently caused by MDR Escherichia coli and K. pneumoniae. The overall in-hospital mortality rate of COVID-19 patients was 46.9% (237/505), while 78.7% (59/75) of patients with bacterial infections died. Infection was significantly associated with death (OR 6.01, 95% CI = 3.03–11.92, p-value <0.0001) and a longer hospital stay (p < 0.0001). Multivariate logistic regression analysis showed that Age (OR = 1.04, 95% CI = 1.03–1.06, p-value <0.0001), Sex male (OR = 1.70, 95% CI = 1.08–2.70, p-value <0.0001), Spo2 (OR = 1.99, 95% CI = 1.18–3.38, p-value = 0.010) and Ferritin (OR = 2.33, 95% CI = 1.37–3.97, p-value = 0.002) were independent risk factors associated with in-hospital mortality. Furthermore, 95.3% (221/232) of patients who were intubated died. Conclusion Our findings demonstrate that bacterial infection due to MDR Gram-negative bacteria associated with COVID-19 has an expressive impact on increasing the case mortality rate, reinforcing the importance of the need for surveillance and strict infection control rules to limit the expansion of almost untreatable microorganisms.